Non-invasive Chemokine Detection: Improved Prediction of Antibody-Mediated Rejection in Donor-Specific Antibody-Positive Renal Allograft Recipients - Mühlbacher, Jakob; Doberer, Konstantin; Kozakowski, Nicolas; Regele, Heinz; Camovic, Sümeyra; Haindl, Susanne; Bond, Gregor; Haslacher, Helmuth; Eskandary, Farsad; Reeve, Jeff; Böhmig, Georg A.; Wahrmann, Markus (Frontiers in Medicine, 2020)
Background: Screening for donor-specific antibodies (DSA) has limited diagnostic value in patients with late antibody-mediated rejection (ABMR). Here, we evaluated whether biomarkers reflecting microcirculation inflammation or tissue injury -as an adjunct to DSA detection -are able to improve noninvasive ABMR monitoring. Methods: Upon prospective cross-sectional antibody screening of 741 long-term kidney transplant recipients with a silent clinical course, 86 DSA-positive patients were identified and biopsied. Serum and urine levels of E-selectin/CD62E, vascular cell adhesion molecule 1 (VCAM-1), granzyme B, hepatocyte growth factor (HGF), C-C motif chemokine ligand (CCL)3, CCL4, C-X-C motif chemokine ligand (CXCL)9, CXCL10 and CXCL11 in DSA-positive recipients were investigated applying multiplexed bead-based immunoassays. Results: Diagnosis of ABMR (50 patients) was associated with significantly higher levels of CXCL9 and CXCL10 in blood and urine and of HGF in blood. Overall, urinary CXCL9 had the highest diagnostic accuracy for ABMR (area under the receiver operating characteristic curve: 0.77; accuracy: 80%) and its combined evaluation with the mean fluorescence intensity of the immunodominant DSA (DSAmax MFI) revealed a net reclassification improvement of 73% compared to DSAmax MFI alone.